Systems approaches to support transitions towards resilient and sustainable farm and food systems - Kumar, Shalander (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Despite significant agricultural production achievements, current food systems fail to deliver adequate nutrition while operating unsustainably and contributing substantially to greenhouse gas emissions. India faces a paradox of food security alongside widespread child malnutrition and low farm incomes. The high heterogeneity in crop yields, climate risks, and household outcomes necessitates a paradigm shift from incremental reforms to complete transformation. Systems approaches enable multi-dimensional optimization across economic viability, human health, and environmental sustainability through integrated analytical tools including vulnerability assessment, whole-farm bio-economic modeling, and value chain dynamics analysis. Evidence from landscape-level interventions demonstrates transformation potential through enhanced water availability, increased cropping intensity, and improved livelihoods. Systemic transformation requires four pillars: research reorientation toward integrated systems thinking, policy repurposing to incentivize sustainable practices, institutional innovations leveraging farmer organizations and agri-tech linkages, and cross-sectoral convergence breaking down departmental silos. Implementation imperatives include real-time monitoring systems, strengthening local food systems, and waste-to-wealth approaches for achieving nutrition security, environmental recovery, and economic viability.